Fabrication of Porous β-Type Ti-40Nb Alloys Incorporated with TiH2 via Powder Metallurgy Processing Route Under Reducing Environment / Siti Mariana Hosnie...[et al.] - Hosnie, Siti Mariana; Ismail, Muhammad Hussain; Yahaya, Mazyan; Haris, Nurul ‘Ain; Iain, Todd (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This work attempts to investigate the influence of TiH2 and processing route on microstructure and mechanical properties of Ti-40Nb alloy. The difference in processing route resulted in various microstructure constituent of β-phase as well as the mechanical properties of the alloy. These differences were beneficial towards the biomedical research to fit with the variability mechanical properties of human bone. The formation of porous and β-rich phase of TiNb was believed to help in lowering the Young’s modulus value that subsequently alleviates the mismatch problem between the implant and human bones. Therefore, this work attempted to synthesize porous and β-phase TiNb alloy via powder metallurgy processing route under inert gas of argon associated with reducing environment of CaH2 as the wicking agent. This route was chosen with the purpose to other processing routes such as Selective Laser Melting (SLM), hot pressing and arc melting techniques. The raw materials with 40 wt% of Nb and 60 wt% of TiH2 composition were mixed, compacted and sintered at 1200 °C using a tube furnace. The result showed that Ti-40Nb alloy with β- rich phase demonstrated a promising low Young’s modulus for about 17 GPa, the compressive strength of 300MPa and porosity of 55% respectively. These results were compared with other processing route results for determination of better established method for Ti-40Nb alloy. An alternative route in processing Ti-40Nb alloy has been successfully demonstrated using low-cost techniques. The use of TiH2 in reducing environment can reduce the problem of impurity uptake, particularly during sintering process.